2019
DOI: 10.1186/s12891-019-2635-8
|View full text |Cite
|
Sign up to set email alerts
|

Infected bone resection plus adjuvant antibiotic-impregnated calcium sulfate versus infected bone resection alone in the treatment of diabetic forefoot osteomyelitis

Abstract: Background Managing with diabetic foot osteomyelitis (DFO) is challenging. Even after infective bone resection and thorough debridement, DFO is still difficult to cure and has a high recurrence rate. This retrospective study aims to compare the outcomes of two treatment methods, infected bone resection combined with adjuvant antibiotic-impregnated calcium sulfate and infected bone resection alone, for the treatment of diabetic foot osteomyelitis. Methods Between 2015 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 32 publications
(40 reference statements)
1
36
0
Order By: Relevance
“…Although local antibiotic treatments are widely used for DFO, there is little high-quality evidence on the appropriate indications, best techniques, proper dosages, types of antibiotics, elution properties or pharmacokinetics [ 63 ]. The most recent published report on this topic is a retrospective review of patients with forefoot DFO who did or did not have perioperative antibiotic-impregnated calcium sulphate implanted [ 64 ]. They found that the antibiotic implant did not improve the rate of, or shorten the time to, healing, nor reduce the postoperative amputation rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although local antibiotic treatments are widely used for DFO, there is little high-quality evidence on the appropriate indications, best techniques, proper dosages, types of antibiotics, elution properties or pharmacokinetics [ 63 ]. The most recent published report on this topic is a retrospective review of patients with forefoot DFO who did or did not have perioperative antibiotic-impregnated calcium sulphate implanted [ 64 ]. They found that the antibiotic implant did not improve the rate of, or shorten the time to, healing, nor reduce the postoperative amputation rate.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the antibiotic implant did not improve the rate of, or shorten the time to, healing, nor reduce the postoperative amputation rate. It did, however, reduce recurrences of DFO, but at the price of about a third of the patients having wound leakage that lasted for a couple of months [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was no recurrence recorded after 12 months. [12] A retrospective study by Noman et al reviewed the effectiveness of using adjuvant calcium sulfate antibiotic impregnated beads and debridement on seventy patients with diabetic foot osteomyelitis showed a 90% infection eradication rate and 81% healing rate after a follow-up of 10 months. [4] The result of high healing rates recorded in these studies could be explained by more residual microorganisms being eradicated by the delivery of a higher concentration of antibiotics directly to the wound.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 40-80% of all diabetic foot ulcers (DFU) lead to diabetic foot infections, [1][2][3][4] 20% of these DFUs go on to develop diabetic foot osteomyelitis (DFO). [1][2][3][4][5] Patients with DFO often require hospitalization for surgical excisional debridement of infected bone and at times the discharge process is delayed as patients await antibiotic sensitivities for long term intravenous (IV) antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 40-80% of all diabetic foot ulcers (DFU) lead to diabetic foot infections, [1][2][3][4] 20% of these DFUs go on to develop diabetic foot osteomyelitis (DFO). [1][2][3][4][5] Patients with DFO often require hospitalization for surgical excisional debridement of infected bone and at times the discharge process is delayed as patients await antibiotic sensitivities for long term intravenous (IV) antibiotics. 6 Prior studies have demonstrated a correlation between increased patient length of stay with an increased susceptibility to acquiring hospital related illnesses and iatrogenic complications, [7][8][9][10][11] as well as creating bottlenecks in the emergency department (ED) for patients awaiting hospital beds.…”
Section: Introductionmentioning
confidence: 99%